Analisis Drive Shaft Serat Karbon/Epoksi Untuk Kendaraan Roda Empat Penggerak Roda Belakang - Firman Alhaffis, Siswandi. B (Techno Bahari, 2018)
Composite applications are required in four-wheel drive vehicles. The drive shaft as a transmitting power and torque from the transmission to the differential. To avoid excessive power consumption in the drive shaft, the drive shaft should be required to have a lighter than a conventional drive shaft (steel). Fuel efficiency can be increased if the weight of drive shaft can be reduced. Another advantage from the use of the drive shaft with a composite material is corrosion resistant. In this study is using the composite carbon fiber/epoxy as a drive shafts for rear-wheel drive vehicle with engine capacity is 1.329 cc has maximum 120 N.m is torque. The length is 785 and is 60 mm diameter were taken from reference SM45C steel drive shaft. The design is using by finite element analysis (FEA) simulation method. Furthermore, the manufacturing process of specimen composite drive shaft to according simulation results recommendations. The research found results of fourteen layers carbon fiber/epoxy for torque of 120 N.m. Replacing the steel drive shaft to carbon/epoxy fibers materials can reduce weight to 51%.